1984
DOI: 10.1111/j.1399-0039.1984.tb02143.x
|View full text |Cite
|
Sign up to set email alerts
|

Histocompatibility antigens HLA‐A, ‐B, ‐DR in Greek patients with Kaposi's sarcoma

Abstract: Thirty-two Greek patients with histologically documented Kaposi's sarcoma, aged 46 to 82 years, were typed for HLA-A, B and DR antigens. None of them was homosexual and they had not been subjected to any immunosuppressive therapy. The study revealed a significant increase of HLA-DR5 (53.1% vs. 21.4%, R.R. 4.1) and a decreased frequency of HLA-DR1 (3.3% vs. 16.6%, R.R. 0.16). An increased frequency of HLA-B18 was also noted (43.7% vs. 20.7% R.R. 2.96). These results indicate that the same positive association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 4 publications
0
21
1
Order By: Relevance
“…An increased frequency of HLA-DR5 was reported in classical, non-HIV-related KS patients as well [21], Mann et al [22] evaluated HLA-DQ antigen frequencies in KS patients and found HLA-DQ 1 to be consistently higher than controls in both the classical non-HIV population and the HIV-positive KS population. They hypothesized that HLA-DQ 1 or a closely linked gene is the MHC KSassociated gene.…”
Section: Discussionmentioning
confidence: 99%
“…An increased frequency of HLA-DR5 was reported in classical, non-HIV-related KS patients as well [21], Mann et al [22] evaluated HLA-DQ antigen frequencies in KS patients and found HLA-DQ 1 to be consistently higher than controls in both the classical non-HIV population and the HIV-positive KS population. They hypothesized that HLA-DQ 1 or a closely linked gene is the MHC KSassociated gene.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors link DR5 with throm bocytopenias in the French population [10] and with LAS in the New York population which is predomi nantly of eastern European and Mediterranean origin [12]. HLA-DR5 has increased frequency in classical Ka posi's sarcoma as well [9]. In the present study, the DRwl2 split of DR5 was associated with HIV infection without Kaposi's sarcoma in the Caucasian population and the African American population.…”
Section: Discussionmentioning
confidence: 48%
“…Papaslerialdes et al [9] re vealed a significant increase in HLA-DR5 in the Greek population with classical Kaposi's sarcoma. Some evi dence may, therefore, exist involving DR5 with the same HLA-linked immunogenetic factoifs) associated with the development of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…(c) Genetic susceptibility ln 1983, ear1y in the AIDS epidemic, the HLA-DR5 haplotype was reported to be associated with the occurrence of Kaposi's sarcoma in homosexual men from New York City (Pollack et al, 1983a;Prince et aL., 1984), an association a1so reported among cases of endemic Kaposi' s sarcoma (Pollack et al, 1983b;Contu et aL., 1984;Papasteriades et al, 1984). Subsequent studies have fai1ed to confirm such an association in either AIDS-related or endemic Kaposi's sarcoma (Melbye et aL., 1987;Brunson et al, 1990;Mann et al, 1990;loannidis et al, 1995;Strichman-A1mashanu et al, 1995).…”
Section: (Iii) Other Infectious Agentsmentioning
confidence: 99%